Planning production and inventories in the extended enterprise a state-of-the-art handbook, volume 1 - Kempf, Karl G.; Keskinocak, Pinar; Uzsoy, Reha.; SpringerLink (New York, NY Springer New York, 2011)
In two volumes, Planning Production and Inventories in the Extended Enterprise: A State of the Art Handbook examines production planning across the extended enterprise against a backdrop of important gaps between theory and practice. The early chapters describe the multifaceted nature of production planning problems and reveal many of the core complexities. The middle chapters describe recent research on theoretical techniques to manage these complexities. Accounts of production planning system currently in use in various industries are included in the later chapters. Throughout the two volumes there are suggestions on promising directions for future work focused on closing the gaps. Included in Volume 1 are papers on the Historical Foundations of Manufacturing Planning and Control; Advanced Planning and Scheduling Systems; Sustainable Product Development and Manufacturing; Uncertainty and Production Planning; Demand Forecasting; Production Capacity; Data in Production and Supply Chain Planning; Financial Uncertainty in SC Models; Field Based Research in Production Control; Collaborative SCM; Sequencing and Coordination in Outsourcing and Subcontracting Operations; Inventory Management; Pricing, Variety and Inventory Decisions for Substitutable Items; Perishable and Aging Inventories; Optimization Models of Production Planning Problems; Aggregate Modeling of Manufacturing Systems; Robust Stability Analysis of Decentralized Supply Chains; Simulation in Production Planning; and Simulation-Optimization in Support of Tactical and Strategic Enterprise Decisions. Included in Volume 2 are papers on Workload and Lead-Time Considerations under Uncertainty; Production Planning and Scheduling; Production Planning Effects on Dynamic Behavior of A Simple Supply Chain; Supply and Demand in Assemble-to-Order Supply Chains; Quantitative Risk Assessment in Supply Chains; A Practical Multi-Echelon Inventory Model with Semiconductor Application; Supplier Managed Inventory for Custom Items with Long Lead Times; Decentralized Supply Chain Formation; A Cooperative Game Approach to Procurement Network Formation; Flexible SC Contracts with Options; Build-to-Order Meets Global Sourcing for the Auto Industry; Practical Modeling in Automotive Production; Discrete Event Simulation Models; Diagnosing and Tuning a Statistical Forecasting System; Enterprise-Wide SC Planning in Semiconductor and Package Operations; Production Planning in Plastics; SC Execution Using Predictive Control; Production Scheduling in The Pharmaceutical Industry; Computerized Scheduling for Continuous Casting in Steelmaking; and Multi-Model Production Planning and Scheduling in an Industrial Environment.
1 Preface
2 The Historical Foundations of Manufacturing Planning
and Control Systems
3 Advanced Planning and Scheduling Systems: The Quest
to Leverage ERP for Better Planning
4 The Transition to Sustainable Product Development and
Manufacturing
5 Uncertainty and Production Planning
6 Demand Forecasting Problems in Production Planning
7 Production Capacity: Its Bases, Functions
and Measurement
8 Data in Production and Supply Chain Planning
9 Financial Uncertainty in Supply Chain Models
10 Field-Based Research on Production Control
11 Collaborative Supply Chain Management
12 Sequencing Strategies and Coordination Issues in
Outsourcing and Subcontracting Operations
13 Inventory Management: Information, Coordination, and
Rationality
14 Pricing, Variety, and Inventory Decisions for Product
Lines of Substitutable Items
15 Managing Perishable and Aging Inventories: Review and
Future Research Directions
16 Optimization Models of Production Planning Problems
17 Aggregate Modeling of Manufacturing Systems
18 Robust Stability Analysis of Decentralized Supply Chains
19 Simulation in Production Planning: An Overview with
Emphasis on Recent Developments in Cycle Time
Estimation
20 Simulation-Optimization in Support of Tactical and
Strategic Enterprise Decisions
Electronic reproduction.
Keywords: Business logistics; Economics; Engineering economy; Industrial engineering; Industrial productivity; Inventory control; Operations research; Production planning